Perancangan Lemari Pintar untuk Menyimpan Bawang Merah Berbasis Arduino Uno R3 untuk Menjaga Kualitas dan Kesegaran Bawang Merah - Jaelani Jaelani; Sudarmono Sudarmono; Moh. Taji Sultoni (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2025)
Technology is now increasingly advanced and developing rapidly. Almost every aspect of human life is now assisted by technology, especially computerized technology. This technology has penetrated almost all aspects of life and significantly increased efficiency in completing work. With the existence of computerized technology, many processes that were previously time-consuming and labor-intensive can now be done more quickly, easily, and efficiently. One example of the application of technology in everyday life is the design of a smart cupboard for storing shallots. This smart cupboard is designed to help shallot farmers and sellers store their agricultural products more efficiently. The working system of this tool is similar to the method of storing shallots in traditional huts, but with more sophisticated technology. This smart cupboard can regulate temperature and humidity automatically, which is very important to maintain the quality of shallots. The optimal temperature for storing shallots is between 25º - 30º C, with air humidity around 50% - 60%. If the temperature or humidity in the cupboard does not match the desired conditions, the system will automatically activate the lights and fans to return the temperature and humidity to the desired level. With this automated control system, shallots can be kept fresh for longer, reducing the damage that typically occurs to shallots due to unstable temperature or humidity. The advantage of this smart cabinet is that it can maintain the quality of shallots for a long time, even when stored in large quantities. This greatly assists farmers and traders in reducing losses due to perishable shallots and increasing the efficiency of shallot storage and distribution.